Risk factors for Diabetic Nephropathy - Villena Pacheco, Arturo (2021)
Diabetic nephropathy (DN) is a public health problem whose prevalence is constantly increasing, it represents a significant economic, social and health burden and its diagnosis is usually late and not routine. Its early and timely diagnosis slows the progression of the disease, improves quality of life, increases life expectancy and reduces the high costs of care. It is characterized by elevated urine albumin excretion (> = 300 mg albumin / g urinary creatinine) and / or an estimated glomerular filtration rate <60 ml / min / 1.73 m2. The pathophysiology of DN is complex, determined by persistent hyperglycemia and includes renal hemodynamic changes, renal medular ischemia, tissue inflammation, and activation of the renin-angiotensin-aldosterone system. Among the non-modifiable factors associated with DN are: sex, chronological age, age at diagnosis of DM2, duration of DM2, family history of DN, ethnicity and genetic factors. Among the modifiable factors are: diabetes education, smoking, high levels of glycated hemoglobin, arterial hypertension, dyslipidemia, abdominal obesity, anemia, retinopathy, neuropathy, and elevated uric acid levels. A review of the literature of the factors associated with DN is carried out and the importance of its early and timely diagnosis is emphasized.